Adamantyl aziridines via aza-Michael initiated ring closure (aza-MIRC) reaction. Issue 8 (23rd February 2017) - Fedotova, Alena I.; Komarova, Tatiana A.; Romanov, Alexey R.; Ushakov, Igor A.; Legros, Julien; Maddaluno, Jacques; Rulev, Alexander Yu.
Abstract: An efficient one-pot synthesis of functionalized adamantylaziridines by aza-Michael initiated ring closure (aza-MIRC) reaction of 1-aminoadamantane with α- halogenated Michael acceptors is described. The reaction goes through an aza-Michael intermediate that undergoes an intramolecular nucleophilic substitution. Expectedly, high pressure exerts a beneficial influence in the case of sterically hindered reagents. Graphical abstract: